Students’ Anxiety Factors in Speaking English (a Case Study at the Third Year Students of SMPN 9 Parepere) - Rafiq, Muhamad (Indo-MathEdu Intellectuals Journal, 2023)
This study was conducted to determine the type of student speaking anxiety that predominantly occurs in English classes and to determine the factors of speaking anxiety faced by third-year students of SMPN 9 Parepare. The design of this study is descriptive qualitative. This study used questionnaires to determine the type of student speaking anxiety that was dominant in English classes totaling 35 students, then used interviews to determine the factors of student speaking anxiety in English classes by selecting a sample of 7 students from each class. Samples are taken using random sampling. The data analysis technique used is qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The results of this study showed that the dominant types of students' speaking anxiety were (1) Communication Apprehension with a score of 1173, (2) Test Anxiety scored 1630, and (3) Fear of Negative Evaluation scored 745. This means that most students worry about failing the speaking test and they still feel worried even though they have prepared well for speaking classes. They also still feel less confident with their appearance in front of the class because of their language competence. The factors of speech anxiety faced by students are influenced by four factors, namely cognitive, psychological, social, and physical factors